Magnetic Particle Imaging in Vascular Imaging, Immunotherapy, Cell Tracking, and Noninvasive Diagnosis. (15th March 2023) - Chandrasekharan, Prashant; Kuo, Renesmee; Fung, K. L. Barry; Saayujya, Chinmoy; Bryan, Jacob; Yousuf, Mariam; Fellows, Benjamin; Colson, Caylin; Huynh, Quincy; Doyle, Owen; Hartley, Allison; Yousuf, Khadija; et al.
Abstract : Magnetic particle imaging (MPI) is a new tracer-based imaging modality that is useful in diagnosing various pathophysiology related to the vascular system and for sensitive tracking of cytotherapies. MPI uses nonradioactive and easily assimilated nanometer-sized iron oxide particles as tracers. MPI images the nonlinear Langevin behavior of the iron oxide particles and has allowed for the sensitive detection of iron oxide-labeled therapeutic cells in the body. This review will provide an overview of MPI technology, the tracer, and its use in vascular imaging and cytotherapies using molecular targets.